Community Quality-of-Life Indicators: Best Cases VI
XXX, 264 p.
Keywords: This book is the sixth in a series covering bet practices in community quality-of-life (QOL) indicators. The cases in this volume describe communities that have launched their own community indicators programs. Elements that are included in the descriptions are the history of the community indicators work within the target region, the planning of community indicators, the actual indicators that were selected, the data collection process, the reporting of the results, and the use of the indicators to guide community development decisions and public policy. .